2020
DOI: 10.1016/j.heliyon.2020.e05057
|View full text |Cite
|
Sign up to set email alerts
|

Psychological states of Bangladeshi people four months after the COVID-19 pandemic: An online survey

Abstract: Background The COVID-19 pandemic essentially imposes psychological effects on people. As the pandemic progresses, people experience psychological trauma gradually, which can change over time. The present study aimed to assess the prevalence of depression, anxiety, and stress among Bangladeshi people four months after the COVID-19 outbreak. Methods An online cross-sectional survey was conducted among Bangladeshi citizens aged ≥18 years from June 1 to June 10, 2020. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
76
5
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(89 citation statements)
references
References 28 publications
5
76
5
3
Order By: Relevance
“…The current COVID-19 pandemic has exerted psychological and financial impacts on many people (Banna et al, 2020;Bodrud-Doza et al, 2020;Islam et al, 2020c;Zubayer et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The current COVID-19 pandemic has exerted psychological and financial impacts on many people (Banna et al, 2020;Bodrud-Doza et al, 2020;Islam et al, 2020c;Zubayer et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have suggested that experiencing a severe infectious disease epidemic increases the prevalence of mental health issues, [12][13][14][15][16][17][18][19][20][21][22] it is difficult to find relevant literature or empirical studies that explore quarantine hotel employees faced with the challenge of psychological resilience. Therefore, this study aims to investigate the mental health status and psychological impact on quarantine hotel employees during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Each subscale contains seven items, and is scored using a 4-point Likert scale ranging from 0 (did not apply to me at all) to 3 (much or mostly applied to me). The depression subscale consists of questions 3, 5, 10, 13, 16, 17 and 21, and the score ranges are as follows: normal/no depression (0-9), mild depression (10-13), moderate depression (14)(15)(16)(17)(18)(19)(20), severe depression (21)(22)(23)(24)(25)(26)(27), and extremely severe depression (28 and above). The anxiety subscale consists of questions 2, 4, 7, 9, 15, 19, and 20, and the score ranges are as follows: normal/no anxiety (0-7), mild anxiety (8)(9), moderate anxiety (10)(11)(12)(13)(14), severe anxiety (15)(16)(17)(18)(19), and extremely severe anxiety (20 and above).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pooled prevalence of anxietyA total of 31 studies reported the prevalence of anxiety during COVID-19 in different samples from South Asian countries[46][47][48][49][50][51][52][53][54][55][56]58,59,[61][62][63][64][65][66]68,69,[71][72][73][74][75][76][77][78][79][80] . These studies used different scales to measureanxiety in respective samples, including the Generalized Anxiety Disorder 7-item (GAD-7) scale (n = 16), Depression, Anxiety and Stress Scale -21 Items (DASS-21) scales (n = 9), Hospital Anxiety and Depression Scale (HADS) (n = 4), Patient Health Questionnaire-4 (PHQ-4) (n = 1), and Self Reporting Questionnaire 20-items (SRQ-20) scale (n = 1).…”
mentioning
confidence: 99%